District-level coverage of interventions in the Integrated Child Development Services (ICDS) scheme during pregnancy, lactation and early childhood in India: Insights from the National Family Health Survey-4 - Avula, Rasmi; Sarswat, Esha; Chakrabarti, Suman; Nguyen, Phuong Hong; Mathews, Pratima; Menon, Purnima (International Food Policy Research Institute, 2018)
India’s Integrated Child Development Services (ICDS) scheme, which was launched in 1975, offers nutrition and health services across the continuum of care in the first 1000 days of life. Universalization was mandated in 2006 and implemented thereafter. This Data Note describes the coverage of core ICDS interventions during pregnancy, lactation and early childhood at the district level in 2016, as seen in the National Family Health Survey-4 (NFHS-4) data from 6401districts of India.